The Mineral Content and Sensory Properties of Injera Made from the Faba Bean, Sorghum and Tef Flour Blend - Mihrete, Yimer (International Journal of Nutrition, 2019)
The effects of 55-70% teff (Eragrostis tef), 20-30% sorghum (Sorghum bicolor) and 5-15% faba bean (Viciafaba) flours blending ratio and fermentation time (24, 48 and 72 h) with custom design on iron, zinc and calcium contents and sensory properties of injera were investigated using 100% teff injera as a control. The mixture of faba bean and sorghum with tef significantly increased the iron, zinc and calcium contents of the blended injera. High iron (22.66 mg/100 g), zinc (23.81 mg/100 g) and calcium (187.25 mg/100 g) contents were obtained from 55% tef, 30% sorghum and 15% faba bean blended injera fermented for 72 h. Sensory acceptability of all blended injera scored a mean rating well above the average, which is an indicative of the goodness as products. The most preferred injera by panelists was produced from tef flour combined with 20% sorghum and 10% faba bean flours fermented for 72 h.
Keywords: Blending ratio; Faba bean; Fermentation time; Injera; Mineral nutrient; Sensory; Sorghum; Tef